The Application of Flipped Classroom Combined With Locus of Control Analysis in Lean Entrepreneurship Education for College Students - Qin, Yueqi; Yan, Runyu; Sun, Youxia (Frontiers in Psychology, 2020)
This paper is to explore the status quo and basic laws of entrepreneurship education at the stage of social development in China, providing a theoretical basis and practical guidance for the cultivation of innovative and entrepreneurial talents in colleges. First, a college entrepreneurship education model based on lean entrepreneurship theory and flipped classroom is established to provide the development of entrepreneurship education with a theoretical framework while improving students' autonomous learning ability. Based on the theoretical basis of the influence of the locus of control on entrepreneurial motivation in the entrepreneurial process of college students, the students who participated in the basic education of entrepreneurship among the sophomores in the first semester of the 2018-2019 academic year of a college in Jiangsu Province are selected as the research object. Then, the effect of lean entrepreneurship education under the flipped classroom mode is analyzed. Before the start of the entrepreneurial basic education course, there is no difference between the pretest scores of the research group and the control group students (P> 0.05). After the course, there is no difference between the posttest scores of the two groups of students (P > 0.05). It can be confirmed that, based on the flipped classroom education mode of halving the actual number of lectures by teachers, the effect of basic education on entrepreneurship for students is not different from the traditional teaching effect. Based on the flipped classroom mode, the number of people who have reached the level of "understand" of the text target task is the highest, and the number of people who can reach the "comprehensive application" level of the high-order target is almost 0. It means that the realization of the high-order target still needs to be strengthened. Lean entrepreneurship education mode is based on lean iteration, which is conducive to promoting the development of entrepreneurship education in China. Based on lean entrepreneurship, combining the flipped classroom teaching mode can ideally achieve the goal of deep learning, which is greatly significant for improving the effectiveness of entrepreneurship education.